PENERIMAAN PANELIS DAN ANALISIS USAHA ES KRIM DENGAN PEWARNA KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) - Putra, Suyudi '; Johan, Vonny Setiaries; Ali, Akhyar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
ABSTRACT This research aimed was to find out the acceptance of panelists on the ice cream with red dragon fruit peel as food additive and to analyzed the business feasibility of the ice cream. Acceptance analysis showed that there significantly no difference between ice cream with red dragon fruit peel and commercial ice cream, that means panelist can accept the ice cream with red dragon fruit as food additive. Business analysis showed that ice cream business with capacity 10 kg will be efficient , with total cost Rp.311,201.48. break even point value were 88.91 cups and can give adding value Rp 70.300,00. Keywords:ice cream, red dragon fruit, business analisist.